Peran Dyandra Promosindo Surabaya Sebagai Event Organizer dalam Indonesia International Motor Show (IIMS) Surabaya 2024 - Inggrid Destrina; Maharani Ikaningtyas (Jurnal Manajemen Bisnis Era Digital, 2024)
Dyandra Promosindo is a subsidiary of PT Digital Inisiatif, part of Kompas Gramedia, operating in the MICE (Meetings, Incentives, Conference, and Exhibitions) sector. The event organizer is responsible for determining the theme and overall concept of the event, which serves as the foundation for all event-related aspects. This study aims to understand the role of Dyandra Promosindo Surabaya as an event organizer in organizing an event, namely the Indonesia International Motor Show (IIMS) 2024 in Surabaya. The findings show that Dyandra Promosindo plays a crucial role in promoting products or company brands through various types of events such as expos or exhibitions. The implications of this study highlight the importance of the role of event organizers in the success of events and the satisfaction of all involved parties.